A Wearable Respiratory Monitoring Device – the Between-Days Variability of Calibration - Heyde, C.; Mahler, H.; Roecker, K.; Gollhofer, A. (International Journal of Sports Medicine, 2015)
The between-days variability in ascertained gain factors for calibration of a wearable respiratory inductance plethysmograph (RIP) and validity thereof for the repeated use during exercise were examined. Consecutive 5-min periods of standing still, slow running at 8 km·h-1, fast running at 14 km·h-1 (male) or 12 km·h-1 (female) and recovery were repeated by 10 healthy subjects on 5 days. Breath-by-breath data were recorded simultaneously by flow meter and RIP. Gain factors were determined individually for each trial (CALIND) via least square regression. Reliability and variability in gain factors were quantified respectively by intraclass correlation coefficients (ICC) and limits of agreement. Within a predefined error range of ±20% the amount of RIP-derived tidal volumes after CALIND was compared to corresponding amounts when gain factors of the first trial were applied on the following 4 trials (CALFIRST). ICC ranged within 0.96 and 0.98. The variability in gain factors (up to ± 24.06%) was reduced compensatively by their sum. Amounts of breaths within the predefined error range did not differ between CALIND and (CALFIRST) (P>0.32). The between-days variability of gain factors for a wearable RIP-device does not show impaired reliability in further derived tidal volumes.
Keywords: reproducibility; ventilation; running exercise; inductance plethysmography